1997
DOI: 10.1071/bt96018
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Patterns in Soil Moisture, Vapour Pressure Deficit, Tree Canopy Cover and Pre-dawn Water Potential in a Northern Australian Savanna

Abstract: The wet–dry tropics of northern Australia are characterised by extreme seasonal variation in rainfall and atmospheric vapour pressure deficit, although temperatures are relatively constant throughout the year.This seasonal variation is associated with marked changes in tree canopy cover, although the exact determinants of these changes are complex. This paper reports variation in microclimate (temperature, vapour pressure deficit (VPD)), rainfall, soil moisture, understorey light environment (total daily irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 0 publications
2
51
0
Order By: Relevance
“…Some irrigation of the TLF occurred during the dry season 2009 to assist with plant development, but after that the VWC follows closely the rainfall pattern with higher VWC (20e25%) during the wet season and lower VWC (10%) during the dry. The VWC reported here is similar to soil water content reported in Duff et al (1997) for natural soils in a northern Australian savanna of the wet-dry tropics, which shows the same seasonal variability and range.…”
Section: Resultssupporting
confidence: 84%
“…Some irrigation of the TLF occurred during the dry season 2009 to assist with plant development, but after that the VWC follows closely the rainfall pattern with higher VWC (20e25%) during the wet season and lower VWC (10%) during the dry. The VWC reported here is similar to soil water content reported in Duff et al (1997) for natural soils in a northern Australian savanna of the wet-dry tropics, which shows the same seasonal variability and range.…”
Section: Resultssupporting
confidence: 84%
“…Stomata of evergreen species may be more sensitive to LAVPD than deciduous species (Duff et al 1997). Evergreen species generally have lower conductivities than deciduous species (Eamus and Prior 2001).…”
Section: Hydraulic Architecture and Photosynthesismentioning
confidence: 99%
“…However, in the tropics, several irrigation experiments in the field have shown little impact of soil water availability on leaf phenology (Wright and Cornejo, 1990;Myers et al, 1998). Several authors have suggested that evaporative demand may also be an important environmental variable controlling leaf phenology (Wright and Cornejo, 1990;Duff et al, 1997;Myers et al, 1998).…”
Section: Introductionmentioning
confidence: 98%